Development of Interactive Learning Media using Autoplay Media Studio 8 for Colloidal Chemistry Material - Jannah, Miftahul; Copriady, Jimmi; Rasmiwetti, Rasmiwetti (Journal of Educational Sciences, 2019)
Chemistry is to study the concepts which are mostly abstract. One of them is in colloidal material. The abstract concepts are difficult to understand if only explained in two-dimensional form. Therefore, a media is needed to visualize the abstract concepts of colloidal material both in terms of both macroscopic and microscopic. This study aims to develop an interactive learning media using Autoplay Media Studio 8 that is worthy of being used as a learning media. The study used the Research and Development (R & D) method which refered to the Borg and Gall model. Data collection techniques were in the form of validation sheets and response questionnaires (teachers and students). The data analysis technique used descriptive statistical analysis. The results show that the percentage score obtained from five experts (two media experts and three material experts) gained 96.74% with very valid categories. The results of trials for teachers and students each obtained an average percentage score of 87% and 92% with very practical categories. Based on the results of the study, it can be concluded that interactive learning media using Autoplay Media Studio 8 on chemistry subjects of colloid material in class XI SMA/MA are appropriate to be used as learning media.